A joint experimental and theoretical study on ZnO nanocomposites synthesised by a liquid deposition method. (1st July 2015) - Mohaghegh, N.; Zeidabadi-Nejad, L.; Tasviri, M.; Dehestani, M.; Haqgu, M.; Gholami, M.R.
ZnO was grown on mordenite zeolite, activated carbon and alumina substrates by a liquid deposition method. The photocatalytic activity of the synthesised samples was elucidated using the photodegradation of Acid Blue 92 (AB92) dyes as a test pollutant under UV light irradiation. Supports play a key role in AB92 photodegradation and significantly improve the photocatalytic activity of ZnO. Different supports form additional transport channels and provide an effective pathway for the charge carriers. The supports effectively construct porous structures with more active sites. Hence, the higher photocatalytic activity of supported catalysts is attributed to the large surface area and charge carrier separation. Bader's AIM theory showed that the strength and nature of intermolecular interactions between ZnO and the various supports is different. All geometry structures were optimised with B3LYP/6-31g (d) level theory. The performed local reactivity descriptors determined the reactive sites in molecules, demonstrating the mechanism for the enhanced photocatalytic activity of the composites. Both experimental and theoretical results confirm that the insertion of ZnO nanoparticles on the supports enhances electron transfer between ZnO and the catalyst surface, thus inhibiting charge recombination. The highest photocatalytic activity was observed for ZnO/MOR nanocomposite due to its high surface area, unique structure of MOR and photonic efficiency.